Questão social : um estudo acerca dos fundamentos teóricos, estratégias metodológicas e relação teórico-prática no ensino em serviço social - Ferreira, José Wesley (2015)
This study discusses the teaching of Social Issues in training in social work, in order to analyze how we are giving the teaching thereof, in relation to the theoretical foundations, methodological strategies and the theory-practice articulation, in order to offer subsidies for the improvement of education in the area. From a methodological point of view, the research is qualitative, elected dialectical and historical materialism as a method that has the following main categories: all, historicity and the contradiction. It employed the case study of a Course of Social Service, linked to a public university in Rio Grande do Sul. Were used for collecting the data, semi-structured interview techniques, whose subjects were fourteen teachers and twelve students that course and document analysis of Project Political. The content analysis technique was used for data processing and analysis. The study results show that the teaching of Social Issues in the Course researched is based on historical and dialectical materialism. However the arrest paradigm occurs in a weakened form, which affects the heterogeneity of concepts and mechanical reproduction of the concept. Teaching strategies of Social Issues range from game approaches, to lectures, preceded by readings. Coordination with the everyday experiences of students was highlighted as a powerful strategy in the teaching of Social Issues. Have the articulation of the social issue with teaching experience as a social worker of teachers was identified with an effective strategy for theoretical and practical grasp of object professional. There are difficulties in understanding of the social issue as the object of professional intervention during the supervised training. This difficulty predates the entry on stage, since the mainstreaming of practice teaching is not included in the teaching of Social Issues in this course. However, students demonstrate approaches in understanding the articulation of theoretical and methodological, technical and operational skills during the supervised training. The field supervisors and academic controversy exists as to the operation of the work, which requires greater coordination of this triad to overcome the challenges of theoretical and practical articulation. The propositions of this study highlight the need to deepen the understanding of the historical and dialectical materialism to overcome the heterogeneity of views on Social Issues, there is need to link the teaching of Social Issues with the everyday experience of students and to mediate the teaching of theoretical relationship -Practice from the experiences of teachers and social workers, both in socio-occupational spaces as extension projects. The improvement of the Social Issues teaching from the theory-practice relationship also requires the development of research to discuss the technical and operational skills, problematize the Social Issues as object and result in academic research on these issues which effectively subsidize training in Social Service.